Two new species of Australoheros (Teleostei: Cichlidae), with notes on diversity of the genus and biogeography of the Río de la Plata basin - Říčan, Oldřich; Piálek, Lubomír; Almirón, Adriana; Casciotta, Jorge (Zootaxa, 2011)
Two new species of Australoheros Ř íčan and Kullander are described. Australoheros ykeregua sp. nov. is described from the tributaries of the río Uruguay in Misiones province, Argentina. Australoheros angiru sp. nov. is described from the tributaries of the upper rio Uruguai and middle rio Iguaçu in Brazil. The two new species are not closely related, A. ykeregua is the sister species of A. forquilha Ř íčan and Kullander, while A. angiru is the sister species of A. minuano Ř íčan and Kullander. The diversity of the genus Australoheros is reviewed using morphological and molecular phylogenetic analyses. These analyses suggest that the described species diversity of the genus in the coastal drainages of SE Brazil is overestimated and that many described species are best undestood as representing cases of intraspecific variation. The distribution patterns of Australoheros species in the Uruguay and Iguazú river drainages point to historical connections between today isolated river drainages (the lower río Iguazú with the arroyo Urugua–í, and the middle rio Iguaçu with the upper rio Uruguai). Molecular clocks are used to date these and other biogeographic patterns.